Decadal (1994–2008) change in the carbon isotope ratio in the eastern South Pacific Ocean. Issue 8 (1st August 2014) - Ko, Young Ho; Lee, Kitack; Quay, Paul D.; Feely, Richard A.
Abstract We determined the 14 year change in the anthropogenic CO2 inventory in the eastern South Pacific Ocean along the 110°W meridian from 67°S to 21°N, using seawater δ13C data sets collected in 1994 and 2008. The vertical integral of the 14 year δ13C change was assessed in five latitude bands and found to be greatest (−14.7‰ m yr−1) in the subpolar band (38°S–55°S) and smallest (−3.0‰ m yr−1) in the tropical band (21°N–18°S). The δ13C change in each of the latitudinal bands was primarily caused by inputs of anthropogenic CO2 via air‐sea exchange and transport. More than 50% of the total anthropogenic CO2 was added to the subpolar band via the northward movement of Antarctic Intermediate Water (AAIW) from the south, and the remaining 50% was added via air‐sea exchange. We also calculated the ratio of the temporal change in δ13C to the change in dissolved inorganic carbon, which is a measure of the efficiency of oceanic uptake of anthropogenic CO2. The ratio for AAIW in 1994 (−0.017‰ (µmol kg−1) −1) was greater than that in 2008 (−0.010‰ (µmol kg−1) −1) based on the change in preformed δ13C and dissolved inorganic carbon (DIC), indicating reduced efficiency of CO2 uptake by the Southern Ocean in 2008 relative to that in 1994. AAIW remained at the surface for a shorter period in 2008 relative to 1994, and thus would have taken up less atmospheric CO2 prior to subduction. The projected reduction in this ratio indicates a weakening of CO2 uptake by the Southern Ocean in the future.